ANALYSIS OF THE SUCCESS LEVEL OF WIRELESS DATA COMMUNICATION PERFORMANCE USING SX1278 TRANSCEIVER AT 433 MHz SPECTRUM - Pratiwi, Anggie; Marpaung, Jannus; Kusumawardhani, Eka (Faculty of Engineering, Universitas Tanjungpura, 2024)
In wireless communication, the success of information exchange is a critical aspect, evaluated based on parameters such as Packet Delivery Ratio (PDR) and packet loss. Several factors, such as antenna gain, antenna height, and transmission distance, if not appropriately configured, can result in a small packet data ratio due to the loss of packets in wireless communication, leading to a lack of received information. Therefore, research has been conducted to identify and understand the causes of a small packet data ratio due to packet loss. The results obtained from this research show a Packet Delivery Ratio (PDR) of 100% and packet loss of 0% with the use of a 3 dBi gain antenna, which is only able to reach a distance of 400 meters. Meanwhile, the use of a 5 dBi gain antenna can reach a distance of 800 meters. Increasing the gain antenna can enhance the transmission distance. In terms of antenna height variation, a 3 meter height achieves a Packet Delivery Ratio (PDR) of 100% and packet loss of 0%, covering a distance of 600 meters, while the use of a 6-meter antenna height can reach a distance of 800 meters. Increasing the antenna height can improve the transmission distance.